Optimization of Protease Activity of Endophytic Bacteria EUA-136 and EUA-139 from Bruguiera gymnorrhiza Using Response Surface Methodology - Agustien, Anthoni; Zovia, Miftahul; Dwitaviani, Rima; Marlida, Yetti (HAYATI Journal of Biosciences, 2025)
Protease is a vital enzyme used in industries such as detergents, pharmaceuticals, and animal feed, with a growing demand in the enzyme market. Endophytic microorganisms can produce stable proteases with a rapid synthesis process. This study optimized conditions of temperature, pH, salinity, agitation, and nutrient sources for protease production by EUA-136 and EUA-139 bacterial isolates. The research used Response Surface Methodology (RSM) with a Central Composite Design (CCD) in Design Expert Software 13.1 to identify optimal conditions and the bacterial isolates. The optimum conditions for the EUA-136 bacterial isolate to produce protease were 3% inoculum at 30 ºC, pH 7, 28.5 ppt salinity, and 150 rpm agitation. For the EUA-139 bacterial isolate, the optimum conditions were a carbon source of 1% (v/v) maltose, a nitrogen source of 1% (v/v) KNO3, casein as the inducer, and an inoculum concentration of 7.5% (v/v). Molecular identification of isolates EUA-136 and EUA-139 revealed similarities to Bacillus cereus strain 3TC-3 and Bacillus paramycoides 3665, respectively.